Factors Affecting Stock Prices With Dividend Policy As An Intervening Variable In Mining Companies Listed On The Idx - Lina, Nur Mey; Fatimah, Fatimah; Ladewi, Yuhanis (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2023)
This study aims to determine and analyze the factors influencing stock prices with dividend policy as an intervening variable in mining companies listed on the Indonesia Stock Exchange. The objects in this study are stock prices, dividend policy, current ratio, debt-to-asset ratio and net profit margin. This research was conducted at Mining Companies listed on the Indonesia Stock Exchange. The research method used in this research is associative. The data used in this research is secondary data. The population in this study were 63 companies, samples obtained through purposive sampling method, namely 21 companies for a period of 5 years with 5 research variables. The data analysis technique used in this study is path analysis by testing direct and indirect effects. The results of the direct effect research show that the current ratio has no significant effect on dividend policy, the debt to asset ratio has a significant effect on dividend policy, the net profit margin has a significant effect on dividend policy, the current ratio has no significant effect on stock prices, debt to asset ratio has no significant effect on stock prices, the net profit margin has a significant effect on stock prices, dividend policy has a significant effect on stock prices. The results of the study show that the current ratio has no significant effect on stock prices with dividend policy as an intervening variable, debt to asset ratio has a significant effect on stock prices with dividend policy as an intervening variable, and net profit margin has a significant effect on stock prices with dividend policy as an intervening variable